Penerapan Logika Fuzzy sebagai Alat Deteksi Hipotermia dan Hipertermia Pada Manusia Berbasis Internet Of Thing (Iot) - Widya Cahyadi; Ali Rizal Chaidir; Muchammad Farhan Anda (Universitas Syiah Kuala, 2021)
Health is an important thing for human life. One way to determine a person’s health can be done by examining vital signs (TTV) to find out clinical signs by measuring the most basic body functions. TTV examination is also useful in determining the appropriate medical planning and can be used to strengthen the diagnosis of a disease. Most of the illness or even death related to environmental exposure temperature can be prevented, but often the victim’s decision is wrong, or the patient’s reporting is delayed. Although a person in good health may experience varying degrees of exposure to heat or cold at different times, a person will be relatively at risk for illness and death in extreme environmental temperatures. One solution to overcome this problem is the use of Internet of Thing (IoT)-based hypothermia and hyperthermia detection tools that can detect disease early so that prevention can be done before it becomes more dangerous. The features of this tool are the measurement of body temperature, heart rate, and the detection of hypothermia or hyperthermia. This study, testing the application of fuzzy logic as a hypothermia and hyperthermia detection tool based on IoT-based body temperature and heart rate. The results of system testing with 10 subjects from instrumentation tools showed the same results as the medical officer’s statement with a 100% success rate.